Institutional Trust as a Mediator between Political Efficacy and Voter Participation - Robby Effendi; Suaidah Lubis; Anggi Mutia Dewi; Tania Salsabila Hasibuan; Dwi Putri; Fransisca Mularia Butar Butar (Ali Institute of Research and Publication, 2026)
This study examines institutional trust as a mediator between political efficacy and voter participation after the 2024 local election in Medan, Indonesia. A quantitative cross-sectional correlational design was used with 275 voters selected through convenience sampling. Data were collected through an online survey measuring political efficacy, institutional trust in the General Elections Commission (KPU), and voter participation. Pearson correlations and mediation analysis with 5,000 bootstrap resamples were applied. The results showed positive associations among all variables. Institutional trust significantly mediated the association between political efficacy and voter participation (B = 0.11, SE = 0.03, 95% CI [0.06, 0.17]) and accounted for 20.5% of the total association, while the direct association remained significant (B = 0.42, 95% CI [0.31, 0.53]). These findings indicate partial mediation: citizens’ confidence in their political competence is associated with participation both directly and through their evaluation of electoral institutional credibility. The study highlights institutional trust as an evaluative mechanism in local democratic participation and recommends strengthening political literacy, transparent election administration, and accessible public communication.